Vitamin D levels and cytokine profiles in patients with systemic lupus erythematosus. (October 2015) - Schneider, L; Colar da Silva, A C; Werres Junior, L C; Alegretti, A P; dos Santos, A S Pereira; Santos, M; Sassi, R; Heemann, B; Pfaffenseller, B; Tavares Brenol, J C; Monticielo, O A
Objectives: To evaluate the expression of Th1, Th2, and Th17 cytokines in patients with systemic lupus erythematosus (SLE), and verify the association between serum cytokine levels and vitamin D concentration. Methods: The sample consisted of 172 patients with SLE. 25-Hydroxyvitamin D (25(OH)D) levels were measured by chemiluminescence and 25(OH)D levels <20 ng/mL were considered to reflect vitamin D deficiency. Serum cytokine levels were measured in once-thawed samples, using a Th1/Th2/Th17 CBA (cytometric beads array) kit. Results: One hundred and sixty-one (93.6%) patients were women and 128 (74.4%) were of European descent. Mean patient age was 40.5 ± 13.8 years, and mean age at diagnosis was 31.5 ± 13.4 years. At the time of study entry, patients had a median (IQR) SLEDAI of 2 (1–4) and SLICC of 0 (0–1). Mean 25(OH)D concentration was 25.4 ± 11.04 ng/mL. Fifty-nine (34.3%) patients had a vitamin D deficiency. No statistically significant associations were identified between cytokine and vitamin D levels. The most significant finding was a positive correlation between INF-α levels and SLEDAI ( r s  = 0.22, p  = 0.04). Conclusion: Although vitamin D deficiencies are highly prevalent in patients with SLE, vitamin D levels were not significantly associated with patient cytokine profiles. The positive correlation between IFN-α levels and SLEDAI showed in this study corroborates other findings in the literature. The present results did not replicate those of in vitro studies of the effect of vitamin D levels on cytokine profiles. Placebo-controlled intervention trials of the effect of vitamin D on cytokine profiles are still required before any definitive conclusions can be drawn regarding the association between these variables.